Trends and factors of botanical dietary supplement use among US adults with COPD from 1999 to 2016 - Sun, Yanjie (PLoS One, 2020)
BACKGROUND: The potential effects of botanical dietary supplements (BDS) in the treatment of asthma have been proposed. However, the evidence of the effects of BDS use among patients with COPD is limited. The objective of our study was to exam the trends and effects of BDS use among US adults with COPD. METHODS: A serial, cross-sectional study was conducted by using data of the NHANSE from 1999 to 2016 (n = 53,348). COPD (n = 2,580) was identified by using self-reported diagnosis history, and any BDS use was identified in the past 30 days. The prevalence of BDS use was calculated for respondents with and without COPD. Simple linear regression models were applied to test for trends in BDS use. Multiple logistic regression models were used to identify the factors of BDS use and patients’ clinical outcomes, including all-cause hospitalization and abnormal hemoglobin levels, associated with BDS use. The results were weighted to represent national estimates. RESULTS: The prevalence of BDS use was greater among participants who had COPD compared to the referent group (mean 16.77% vs. 15.11%, p = 0.044). The trend of BDS use decreased from 1999 through 2016 in COPD group (p = 0.0023), but the trend remained stable in the non-COPD group (P>0.05). Results of multivariate logistic regression models showed that patients with higher family income (≥100% FPL) and graduated from college were more likely to use BDS compared with non-users. BDS use was associated with a lower likelihood of having all-cause hospitalization (adjusted odds ratio = 0.64; 95% CI 0.45–0.92) and abnormal levels of hemoglobin (adjusted odds ratio = 0.67; 95% CI 0.49–0.92) among adult COPD patients, after adjusting for covariates. CONCLUSIONS: The overall use of BDS decreased during 1999 through 2016 for US adults with COPD. The potential benefit of these supplemental medications use for clinical outcomes might exist for adult COPD patients.